Australian SME adoption of cloud computing: drivers and challenges. (3rd August 2022) - Fakieh, Bahjat; Busch, Peter; Blount, Yvette
Adopting cloud services may increase opportunities for achieving competitive advantage and improving business outcomes - this is significant to Australian small and medium-sized enterprises (SMEs) which account for 96% of all Australian organisations. This work explored via a semi-structured survey - the possible drivers and challenges for Australian SMEs adopting cloud computing, to achieve a competitive advantage. Some 470 Australian SMEs were sampled in six Australian cities: Sydney, Melbourne, Brisbane, Canberra, Wollongong, and Newcastle. A conceptual framework was developed using resource-based theory (RBT) together with the technology, organisation and environment (TOE) framework. This work provides an objective benchmark concerning the drivers and challenges when SMEs adopt cloud computing, however we restrict ourselves to the Australian context.